Economic Disaster Management Impact Towards Retail Property: Boycott Movement - Mohd Zaki, Muhammad Amirul Mukmin; Eni, Sabariah (Research in Management of Technology and Business, 2025)
This study investigates the impact of economic disasters, specifically boycott movements, on the retail property sector in Malaysia, with a focus on commercial real estate such as fast-food outlets. The increasing prevalence of socio-political consumer actions, such as the boycott of businesses associated with Israeli-linked products, has led to widespread disruptions across Malaysia’s food and beverage industry, exemplified by the temporary closure of over 100 KFC outlets. Drawing from qualitative data collected through interviews with six real estate agents and two property owners, this research explores how economic disasters influence rental income, tenant stability, property values, and stakeholder decision-making. Thematic analysis identified four major impact areas: economic performance, occupancy and tenant dynamics, property value and market perception, and socio-psychological effects. Findings indicate a significant decline in occupancy rates and rental income, rising investor uncertainty, and shifts in consumer preferences towards local brands. Property owners adopted mitigation strategies such as rent reductions, flexible leasing, and portfolio diversification. The study highlights the interconnected challenges faced by stakeholders during economic disruptions and calls for the integration of resilient property management practices, stakeholder engagement, and adaptive business strategies to enhance the sector’s long-term sustainability and disaster preparedness.